The Impact of Overconfidence and Regret on Investment Decision - Bebasari, Nataliana; Rakhmat, Adrianna Syariefur (Universitas Pamulang, 2023)
Over the last three years, there has been an increase in Single Investor Identification in the Indonesian capital market. This demonstrates that investor interest and awareness are increasing. To avoid the risk of loss, investment decisions must be made carefully. The purpose of this research is to determine the impact of overconfidence, experienced regret, and investment decisions. This study's sample was drawn using a non-probability sampling method with a purposive sampling technique, and it included 79 investors with Jakarta addresses as respondents. Techniques for collecting data include distributing questionnaires in the form of a Google form. According to the findings of this study, overconfidence has a significant positive effect on investment decisions. Regret has a significant positive impact on investment decisions.